Pregnant Woman Class and Parity to Improving Mother's Health towards Success of SDG's 2030 at Sopaah Public Health Centre in Pamekasan District - Pratiwi, Sari; Peristiowati, Yuly; Koesnadi (Journal for Research in Public Health, 2020)
The high maternal mortality rate associated with pregnancy, childbirth, perinatal care and babies is one of the major problems in Indonesia. Because this mortality rate shows a picture of health status in an area, as an illustration of Indonesia's human development index. The aim of the study was to analyze the classes of pregnant women and parity in improving maternal health towards success in SDG's 2030 at the Sopaah Community Health Center in Pamekasan Regency. The research design was Cross Sectional. The population was all postpartum mothers. The sample size is 104 respondents using Simple Random sampling technique. Independent variables was classes of pregnant women and parity. Dependent variables are complications of pregnancy, postpartum care, and initiation of early breastfeeding. Data were collected using a questionnaire, data were analyzed using logistic regression test (α ≤ 0.05). The results showed that there were influences between the classes of pregnant women with complications of pregnant women (p = 0.036), and there was no effect of parity on complications of pregnant women (p = 0.321). There was no influence between the classes of pregnant women (p = 0.997) and Parity (p = 0.379) with postpartum care. There was no relationship between classes of pregnant women (p = 0.059) and Parity (p = 0.447) with early initiation of inclusion. Classes of pregnant women affect the complications of pregnant women, the full participation of pregnant women can be carried out in an effort to prevent pregnant women from reducing complications of pregnant women, so that the health of mothers and babies is getting better